Exploring theories and expanding methodologies where we are and where we need to go - Barnartt, Sharon N.; Altman, Barbara Mandell (Research in social science and disability ;, 2001)
This volume of "Research in Social Science and Disability" focuses attention on the dual themes of theory and methodology that must form a basis for studies of impairment and disability. It addresses issues that include: critiques of current concepts of disability; the fit between sociological role theory and the concept of disability; the operationalization of different definitions of disability; conducting surveys with people with impairments; and, the reliability and utility of several qualitative research methodologies as applied to impairment and disability. Overall, the papers in this volume represent the beginning of a resurgence of interest in social science theories and methodologies within the study of impairment and disability.